Prevalence of Bovine Mastitis Pathogens in Bulk Tank Milk in China. - Yanliang Bi; Ya Jing Wang; Yun Qin; Roger Guix Vallverdú; Jaime Maldonado García; Wei Sun; Shengli Li; Zhijun Cao (PLoS ONE, 2016)
The objectives of this study were to estimate the herd prevalence of major mastitis pathogens in bulk tank milk (BTM) in China dairy herds, to determine the relationship between the presence of mastitis pathogens and bulk tank milk somatic cell counts (BTSCC), and to investigate the impact of different dairy cattle farming modes and region on bacterial species. BTM samples collected from 894 dairy herds in China were examined for the presence of mastitis pathogens. The Flinders Technology Associates (FTA) cards were used for BTM sample collection, storage, and transportation and bacterial DNA amplification by real-time PCR. Among contagious pathogens, Staphylococcus aureus, Streptococcus agalactiae, and Streptococcus dysgalactiae were detected in 50.1, 92.2, and 72.3% of the 894 BTM samples, respectively. Among environmental pathogens, E. coli, Streptococcus uberis, Enterococcus spp., Klebsiella spp., Serratia marcescens, Corynebacterium bovis, and Arcanobacterium pyogenes were detected in 28.6, 8.9, 35.7, 20.0, 1.3, 17.0, and 67.2% of the BTM samples, respectively. Staphylococcal β-lactamase gene was detected in 61.7% of the BTM samples. The presence of Staphylococcus aureus and Arcanobacterium pyogenes were significantly associated with high BTSCC, respectively. Significant differences were found in presence of Staphylococcus aureus, Streptococcus agalactiae, and Streptococcus dysgalactiae in BTM sampled from the small household farms, dairy-farming communities, and large-scaled dairy farms. There were significant differences in the presence of Streptococcus agalactiae, Streptococcus dysgalactiae, Arcanobacterium pyogenes, staphylococcal β-lactamase gene, Staphylococcus spp., Klebsiella spp., Enterococcus spp., and Streptococcus uberis in BTM among Inner Mongolia, Heilongjiang, and Hebei province. In conclusion, contagious mammary pathogens are predominated among pathogens in BTM samples in China.